2019
DOI: 10.1016/j.tcb.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Intersections between Regulated Cell Death and Autophagy

Abstract: Mutations in Lef1 occur in human and mouse sebaceous gland (SG) tumors, but their contribution to carcinogenesis remains unclear. Since Gata6 controls lineage identity in SG, we investigated the link between these two transcription factors. Here, we show that Gata6 is a b-catenin-independent transcriptional target of mutant Lef1. During epidermal development, Gata6 is expressed in a subset of Sox9-positive Lef1-negative hair follicle progenitors that give rise to the upper SG. Overexpression of Gata6 by in ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 210 publications
1
57
0
Order By: Relevance
“…Second, we did not assess components of other cell death pathways to investigate whether more than one pathway may be involved in the observed cell death. This may be relevant as there are reports of intersections and cross‐talk between different pathways (reviewed in Napoletano et al and Song et al). Furthermore, in the in vitro studies, the menisci were cultured in the absence of mechanical loading, which has been reported to disrupt homeostasis of the medial meniscus differently than the lateral .…”
Section: Discussionmentioning
confidence: 96%
“…Second, we did not assess components of other cell death pathways to investigate whether more than one pathway may be involved in the observed cell death. This may be relevant as there are reports of intersections and cross‐talk between different pathways (reviewed in Napoletano et al and Song et al). Furthermore, in the in vitro studies, the menisci were cultured in the absence of mechanical loading, which has been reported to disrupt homeostasis of the medial meniscus differently than the lateral .…”
Section: Discussionmentioning
confidence: 96%
“…the involvement of caspases and various Bcl-2 protein family members [5,74,75], the initiating events -and how the various components of the UPR integrate on them -are less well defined. Moreover, the role played by autophagy and ATG proteins, which are very often implicated in cell fate decisions [28], is uncertain. Numerous studies have shown that ER stress-induced cell death-initiation involves death receptor-associated activation of caspase-8 [9, 13, 17-22, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy and autophagy-related (ATG) proteins are frequently implicated in cell death regulation [28], but their role in ER stress-induced cell death is unclear. ER stress potently upregulates the expression of microtubuleassociated proteins 1A/1B light chain 3B (LC3B), as well as other ATGs [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, autophagy is crucial for maintaining cellular homeostasis and plays a prosurvival role. 12,13) In other cases, autophagy can induce a prodeath signal pathway. 14) Therefore, autophaghy can determine cell fate.…”
Section: Introductionmentioning
confidence: 99%